Advances and challenges in the field of plasma polymer nanoparticles - Choukourov, Andrei; Pleskunov, Pavel; Nikitin, Daniil; Titov, Valerii; Shelemin, Artem; Vaidulych, Mykhailo; Kuzminova, Anna; Solař, Pavel; Hanuš, Jan; Kousal, Jaroslav; Kylián, Ondřej; Slavínská, Danka; et al. (Beilstein journal of nanotechnology, 2017)
This contribution reviews plasma polymer nanoparticles produced by gas aggregation cluster sources either via plasma polymerization of volatile monomers or via radio frequency (RF) magnetron sputtering of conventional polymers. The formation of hydrocarbon, fluorocarbon, silicon- and nitrogen-containing plasma polymer nanoparticles as well as core@shell nanoparticles based on plasma polymers is discussed with a focus on the development of novel nanostructured surfaces.
Keywords: gas aggregation cluster source; nanoparticles; nanocomposite; sputtering; plasma polymer